Unravelling the K-promotion effect in highly active and stable Fe5C2 nanoparticles for catalytic linear α-olefin production. Issue 3 (22nd January 2021) - Lee, Jin Hee; Lee, Hack-Keun; Kim, Kwangsoo; Rhim, Geun Bae; Youn, Min Hye; Jeong, Heondo; Park, Jong Hyeok; Chun, Dong Hyun; Kim, Byung-Hyun; Park, Ji Chan
Abstract : The K-doped Fe5 C2 @C/NPC nanocatalyst shows excellent performance with high selectivity and productivity for catalytic linear α-olefin production. Abstract : C5 –C13 linear alpha(α) olefins (LAOs) are high-value-added chemicals acknowledged by industry. However, using catalysts to elevate the activity and selectivity of LAOs remains a major challenge for Fischer–Tropsch synthesis (FTS). Recently, researchers on catalyst design have reported enhanced LAO production via FTS, but a more detailed understanding of the electron interactions between the active particles and hydrocarbon products is still needed. In the present paper, we report theoretical and experimental results of a potassium (K)-promotion effect on an optimized iron-carbide nanocatalyst ( i.e. a carbon-encapsulated iron-carbide nanoparticle supported on nitrogen-doped porous carbon: Fe5 C2 @C/NPC). The K-doped Fe5 C2 @C/NPC nanocatalyst shows excellent catalytic performance with a high CO conversion of up to 96.7% at 78 h time-on-stream, C5 –C13 LAO selectivity of 16.5% and productivity of 5.9 CH2 μmol gcat −1 s −1, compared to those of the K-free Fe5 C2 @C/NPC catalyst. The computer simulation model also supports the positive effects of the catalyst with a small amount of K ( ca. 1 wt%, K/Fe = 0.05) in the FTS reaction, which well-matched the experimental results.